Pembangunan Sistem Marketplace Yang Dapat Merekomendasikan Grup Facebook Yang Sesuai Dengan Produk Menggunakan Algoritme Cosine Similarity - Ahmad Wildan Mukafi; Achmad Arwan; Denny Sagita Rusdianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The rapid development of information technology makes humans creating a new innovation in terms of technology. Marketplace is a result of the current technological advances. Marketplace is a place or a container to do product marketing or service through internet media. Over time the competition between products will increase, therefore it needs an advertising trick which can reach more target buyers who are appropriate towards the products. Nowadays, Facebook's being a social media which is pretty much used. Facebook has features which assessed the grup that be able to help advertising the product in accordance with the target of the product. To solve the problem above, a marketplace system which is already integrated with Facebook is required, by using cosine similarity algorithm then products will comprehend the level of similarity from the grup that have been existed. The results of the need analysis has been done, obtained fourty oe of the functional requirements and one non functional requirements. The test which is conducted in this research is the white box and black box testing. White box testing on eight different operating all getting the 100% valid and in accordance with the requirement analysis has been made. While black box testing that has been done on the fourteen testing with the Equivalence Partitioning method the results are 100% valid. As such the functionality test result can be said to be very good and compliance with the essential analysis